Perceptions on soil macrofauna in the agricultural field. - DUDAS, R. T. (2021)
In this study we have evaluated social perceptions on soil macrofauna among farmers and other stakeholders working in an agricultural context in Brazil. During the National No-Tillage Meetings of 2008 and 2018, we have interviewed a total of 171 people (87 in 2008 and 84 in 2018), where 35 percent were farmers (33 percent in 2008, and 36 percent in 2018). A questionnaire with 12 questions was used to determine the profile of interviewees, their soil management practices and perceptions regarding soil macrofauna. From a list of nine soil organisms only earthworms, spiders and centipedes, generally, were not considered pests. When asked about pest incidence, 61-73 percent of the interviewees noticed an increase, mostly related to the excessive use of pesticides (25-33 percent) and monocultures (38-55 percent) for both years. When asked about soil health indicators, more than 80 percent mentioned the presence of a large number of taxa, even including some that were considered pests earlier. The results showed a significant increase in pest incidence after 10 years, together with a decreasing trend in prevalence of good practices. This is profoundly worrisome and highlights the urgent need to foster capacity building and to stimulate more effort in dissemination of information about the importance and function of soil biodiversity, and their vast benefits to society.